Corporate ownership and control contestability in emerging markets: The case of Colombia (2009)
This study examines the structure of voting control and blockholders' contestability for a sample of 233 non-financial listed firms in Colombia during 1996-2004. Corporate control is characterized by high ownership concentration and blockholder power, which implies low separation ratios between cash flow rights and voting rights. On average the separation ratios for the largest voting block is 0.95, while that for the fourth largest shareholder is 0.75. Corporate control is privately biased when there is direct monitoring of firm management by controlling owners. Regression results show that a more equal distribution of equity among large blockholders has a positive effect on firm value. Contestability matters most when firm shares are liquid and actively traded on the stock market. This finding is reinforced when the probability that the largest block can form a winning coalition decreases and performance variables, such as market to sales ratio and return on equity, are included in the estimating equations as substitutes for firm value. In addition, our estimations provide evidence that diversion of rents (tunneling) is limited by blockholders' contestability. © 2008 Elsevier Inc. All rights reserved.